THE SPECIFICATIONS OF ENERGY MODULES IN LIFE SYSTEMS INTEGRATING RELIGIOUS VALUES ON STUDENTS’ SCIENTIFIC LITERACY - Elvi Kurniasih; leny heliawati; Irvan Permana (Indonesian Journal of Science and Education (IJOSE), 2021)
This study aims to analyze the specifications of energy modules in life systems integrating religious values on students’ scientific literacy. The research method uses a quasi-experimental design with a one-group pretest and posttest, with 50 seventh grade students in Islamic-based schools as research subjects. The data obtained were then analyzed using quantitative descriptive. The results of this study indicate that the application of energy modules in living systems integrating religious values is effective on the scientific literacy of students based on the average n-gain score of 0.44 which falls into the medium category. The scientific literacy competence of students in this study sequentially from the highest is to explain scientific phenomena with a percentage of 68.62%, then interpret data and scientific evidence with a percentage of 53.64%, and evaluate and design scientific investigations with a percentage of 41.67 %. Learning by using this module can improve students’ learning outcomes by making learning situations more active so that it is easier to understand the concept of energy in living systems. The research concludes that the application of energy modules in life systems integrating religious values is effective on students’ scientific literacy.